Shobha De's Novels and the Determinants of Liaison: An Analysis of the Human Psyche - Tharu, Raj Kumar (Academia Research Journal, 2023)
This paper presents an analysis of how Shobha De portrays the innate human inclination towards prioritizing oneself in practical situations. In a majority of her novels, De aims to reveal the true reality of her characters, which many other authors inadvertently hide beneath the surface. The study also examines the factors and circumstances that significantly influence the development of human relationships as a consequence of individuals' self-centred tendencies. The author, in her works, gives her female characters the chance to define humanity, including themselves. Her reasoning is based on her belief that romantic relationships are intrinsically linked to the human tendency to emphasize one's own desires and needs. As a result, people have a self-centred psychological attitude regardless of their gender. She portrays the women as the leading characters, possessing a psyche that desires complete freedom in both their personal and social lives. To explore the human nature of self-interest in the context of establishing relationships, this qualitative research paper employs the Freudian theory of psychoanalysis and some of its interpretations by renowned literary scholars. The primary sources for this research were some of Shobha De's novels, while the secondary sources included both online and offline materials written about her major works of fiction. The study concludes that Shobha De's fictional works demonstrate that liaisons are determined by inherent human psychological factors of self-interest and egotism.